Мedia Text: Communication Tactics for Building Trust - Alla N. Teplyashina (Гуманитарный вектор)
Using the activities example of journalist-podcaster, Kommersant media holding expert Daria Tsivina, the article examines communicative tactics for building trust as an media culture integral part. One of the main reasons for the article topic relevance is the transformation of the formation processes and trust manifestation in a journalist associated with the development of information and communication technologies and convergence processes. Media trust is a key concept in the overall assessment of the journalistic text quality. We show the relationship between the main trust elements, which is understood as the truthfulness of words, actions, emotions and motives. The article presents the empirical study results, the purpose of which is to identify journalistic communication tactics that are of particular importance in the media trust formation. Nonverbal communication – voice intonation – is the most important, along with verbal, means of communication and influence. The features of nonverbal communication compared to verbal communication are described.Leading qualities determined based on the study results are indicated, which include speech skills (speech technique), communication skills (speech logic, emotional content); persuasiveness, ability to present information; erudition. To achieve the study purpose, an online survey was conducted. The research process used the content analysis method, as well as lexical-semantic and morphological analysis. It is concluded that the podcast is an audio version of a written text. This is one of the main differences between the podcast format and other formats of modern media discourse, which allows us to explore the author’s speech techniques. It can be concluded that the Tsivina’s texts lexical features show that the restaurant critic views his own podcast as an effective means of communication with the audience. In general, the podcast “Restaurant Criticism with Daria Tsivina” is characterized by a clear, concise structure and the use of easy-to-understand morphological units. Prosody as a super segmental phonological phenomenon in context. This study suggests that the podcaster must take into account prosody as a super segmental phonological phenomenon that is critical to the trust formation.